FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN KEHAMILAN YANG TIDAK DIINGINKAN (KTD) PADA REMAJA DI KABUPATEN MAJALENGKA JAWA BARAT - lisnawati lisnawati; Raika Padmawati (JURNAL MEDIA KESEHATAN, 2022)
Problems: In Majalengka Regency, cases of unwanted pregnancy in adolescents are increasing, from the Majalengka Health Office, it was found that the cases of unwanted pregnancy in 2018 were 251 cases and in 2019 there were 263 cases. cases, the majority of these cases occurred in the age range 15-18 years. Of the 31 Districts in Majalengka Regency, there are 5 districts that have the highest incidence of unwanted pregnancy, namely in Sumberjaya District, Salagedang District, Sindangwangi District, Majalengka District, and Panyingkiran District. The aim of the research : to determine the factors that influence the incidence of unwanted pregnancies in adolescents in Majalengka Regency. Research Method: a quantitative study, with a case control approach. The population is all pregnancies during adolescence in Majalengka Regency, amounting to 195 people. Sampling in the case group used a total sampling technique with a total sample of 25 cases and control with a proportional random sampling technique with a total of 25. The analysis technique used chi Square and simple logistic regression. The Results: Relationship between premarital sexual behavior and unwanted pregnancy in adolescents (p value = 0.00), the relationship between knowledge of unwanted pregnancy in adolescents (p value = 0.259 and OR = 0.3430), the relationship between access to information media and unwanted pregnancy in adolescents (p value = 0.793 and OR = 0.750), the relationship between parenting style and unwanted pregnancy in adolescents (p value = 0.00 and OR 31.5. Conclusion: There is a relationship between premarital sexual behavior, parenting style, and peer influence with the incidence of unwanted pregnancy in adolescents. There is no relationship between adolescent knowledge and access to information media with the incidence of unwanted pregnancy among adolescents.